2020
DOI: 10.1016/j.heliyon.2020.e05737
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi alter antifungal potential of lemongrass essential oil against Fusarium solani, causing root rot in common bean (Phaseolus vulgaris L.)

Abstract: The variation in chemical composition of essential oils (EOs) as affected by plant phenology and environmental factors is a crucial limitation in standardization of EOs and thus their effective implementation into novel organic farming. The cultivation of medicinal and aromatic plants (MAP) using bio-elicitors has been advocated as genuine tool to sustainably assure higher quantity and quality EOs. Herein, a field trial and laboratory bioassays were undergone to decipher the impact of a local arbuscular mycorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…The results demonstrate the benef icial ef fect of the interaction between AMF and leachate against pathogenic fungi such as Cercospora personata, in this sense, Eke et al (2020) corroborate that AMF inoculation changed the biochemical processes of the bean plant (Phaseolus vulgaris L.) with a subsequent impact on growth and greater suppression of root rot by Fusarium under greenhouse conditions.…”
Section: Pre-harvest Evaluationsupporting
confidence: 67%
“…The results demonstrate the benef icial ef fect of the interaction between AMF and leachate against pathogenic fungi such as Cercospora personata, in this sense, Eke et al (2020) corroborate that AMF inoculation changed the biochemical processes of the bean plant (Phaseolus vulgaris L.) with a subsequent impact on growth and greater suppression of root rot by Fusarium under greenhouse conditions.…”
Section: Pre-harvest Evaluationsupporting
confidence: 67%
“…Compared with the control without AMF inoculation, the disease index and incidence of Ralstonia solanacearum inoculated with G. rhizogenes and G. mossie were reduced by 9.7% and 49.8%, respectively [ 23 ]. G. asciculatum , G. etunicatum , G. macrocarpum , G. Margarita , G. heterogama, and G. calospora in AMF can reduce the diseases caused by pathogenic fungi of the genera Pythium , Phytophthora , Fusarium , Rhizoctonia , Macrophomina , Pyrenochaeta , Thielaviopsis , Phoma , Cylindrocarpum , Ophiobolus , and Sclerotium in barley, peanut, soybean, banana, cotton, kidney bean, onion, tobacco, citrus, peach, poplar, strawberries, red clover, and ginseng [ 24 , 25 , 26 , 27 , 28 , 29 ]. Sudhasha et al [ 30 ] found that G. intraradices inhibited the growth of the pathogenic fungus F. oxysporum and proposed that the chemical balance of mycorrhizae inhibited the growth and reproduction of pathogenic fungi.…”
Section: Biocontrol Of Amf Against Phytopathogenic Fungimentioning
confidence: 99%
“…First, the concentration of each constituent EO of the ternary formu-lation at 600 times dilution was only 0.0556 g/L, while that of the binary formulation was 0.0833 (approximately 1.5 times higher). Secondly, at this dilution, the low concentration (0.0556 g/L) of lemongrass oil, garlic oil and mustard oil contained in the ternary formulation might be lower than the minimal inhibitory concentration (MIC) needed to effectively inhibit the growth of F. incarnatum (Dutta et al, 2021;Eke et al, 2020;Wang et al, 2020). Particularly, MIC for controlling Fusarium solani of lemongrass oil was 0.5 g/L (Eke et al, 2020), while MIC against Fusarium oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%